100 % lolos SBMPTN : seleksi bersama masuk perguruan tinggi negeri IPA saintek / Ratih Putri Pratiwi...[et al] ; penyunting, Noni Rosliyani...[et al] ; ilustrasi, Ayu Hapsari - Ratih Putri Pratiwi; Noni Rosliyani; Ayu Hapsari (B-First, 2015)
xi, 90 hlm. : ilus. ; 28 cm